IMPLEMENTASI PENDEKATAN POLA GERAK DOMINAN DALAM PEMBELAJARAN AKTIVITAS SENAM ARTISTIK:PTK di SMA Negeri 2 Tasikmalaya - Dicki Febriansyah, - (2012)
Against the background of this research by the importance of applying dominant motion patterns in the learning activities of artistic gymnastics. Central issue in this study is the low ability students in applying an understanding of the artistic gymnastics skills to approach the dominant motion patterns in SMA Negeri 2 Tasikmalaya, so it can be known to the student's ability in terms of cognitive, affective, and psychomotor. The purpose of this study is to improve the quality of teaching learning penjas primarily on artistic gymnastics through dominant motion patterns in SMA Negeri 2 Tasikmalaya. The samples used in this study that students in grade XI (Eleven) with a total sample of one class of 35 people from District 2 high school student population Tasikmalaya class XI (Eleven) with lots of classes totaling 9 classes totaling 340 people. The research method used is a Class Action Research (PTK) which is 3 months old study by the division of the first cycle and second cycle and the number of cycles each one of 7 action and suklus 2 is 3 actions The writer concluded: 1) Implementation of the dominant motion patterns on learning artistic gymnastics at the SMA Negeri 2 Tasikmalaya in terms of cognitive aspects, namely the ability of students to be active in learning and knowledge physical education artistic gymnastics either use or not to have been delivered by teachers and students are able understand it. 2) Implementation of the dominant motion patterns on learning artistic gymnastics is obtained in terms of the affective aspects that students are able to perform basic movements. 3) Implementation of the dominant pattern of motion in terms of artistic gymnastics learning of psychomotor aspects in accordance with targetan the student's ability to perform basic movement in artistic gymnastics most students are able to move so that the basic motor skills of students to meet the psychomotor aspects of the students has been reached. Suggestions in this study are as follows 1) For schools, is expected to provide various support to the learning process 2) For the teacher, is expected to continue to improve its ability to manage the classroom in order to be good governance. 3) For students, are expected to have the motivation to learn better. 4) For the elderly, is expected to help to support students by providing motivation to learn